Articulate Storyline 3, learning media, learning outcomes, arts and culture. - Jumali Jumali; Syamsunir Syamsunir; Hasanuddin Hasanuddin; Abd Kahar (Universitas Muhammadiyah Enrekang, 2025)
This study examines the effectiveness of Nearpod-based learning media in enhancing the biology learning outcomes of 11th-grade students at UPT SMA Negeri 10 Sidenreng Rappang. The research employed a quasi-experimental design with a one-group pretest-posttest format. The sample consisted of 45 students who participated in the study. Data were collected using pretests and posttests to assess the students' understanding of the biology concepts, particularly in the topic of respiratory systems. The findings revealed a significant improvement in students’ learning outcomes, as evidenced by an increase in average test scores from 43.12 in the pretest to 81.75 in the posttest. This indicates that Nearpod, as an interactive learning platform, has a positive effect on students' engagement and comprehension, making it a valuable tool in modern educational settings. The study recommends integrating technology-based media, such as Nearpod, in the teaching and learning process to foster better learning experiences and outcomes for students.